Analisis Faktor Penyebab Terjadinya Kredit Macet pada PT Bank Rakyat Indonesia (Persero) Tbk Unit Sangasanga Periode Tahun 2015-2018 - Sabri Nurdin; Khairil Akbar; Risma Noormawati (Jurnal EKSIS, 2022)
This research aims to analyze and determine the effect of 5C Principles, namely: Character (X1), Capacity (X2), Capital (X3), Collateral (X4), and Condition of Economy (X5) on bad credit (Y) at PT Bank Rakyat Indonesia (Persero) Tbk Sangasanga Unit for the period 2015-2018. This research was conducted in Sangasanga District, Kutai Kartanegara Regency. In this research using primary data obtained from the distribution of the Sangasanga Unit BRI customer questionnaire as many as 100 respondents. Sampling is done by probability sampling technique using Slovin formula. The type of data in this study is quantitative data and uses the method of multiple linear regression analysis analyzed in statistics with the help of SPSS version 23. Testing of the hypothesis used is a partial statistical test (t test) and simultaneously (f test). Partial test results in this study indicate that Character has a positive and significant effect on bad credit, Condition of Economy has a positive and significant effect on bad credit, while Capacity has a negative and not significant effect on bad credit. Capital has a negative and insignificant effect, Collateral has no effect negative and not significant to the existence of bad credit. Simultaneous test results show a significance value of 0,000 which means that Character (X1), Capacity (X2), Capital (X3), Collateral (X4), and Condition of Economy (X5) have a joint effect on bad credit (Y) on PT Bank Rakyat Indonesia (Persero) Tbk Sangasanga Unit.